On the Writing of Natural Imagery in "House by Day, House by Night" - Zhi, Peiyu (Transactions on Social Science, Education and Humanities Research, 2024)
Olga Tokarczuk is a well-known female writer in Poland, whose works often reflect the deep meaning of reality through the description of daily things, and "House by Day, House by Night" is her masterpiece. The imagery in the work involves the grand natural world, from the cosmic celestial bodies to the earthly creatures. By observing celestial bodies, Tokarczuk uses the sun and moon to hint at the change of day and night and the laws of change and immutability in the universe, and uses comets as metaphors for natural and man-made disasters. By focusing on the earth, Tokarczuk uses forests as a sanctuary for natural life, using the dual perspective of the valley to demonstrate the close relationship between nature and people. Through dialogue with living beings, Tokarczuk reflects the laws of nature through the words and deeds of the old woman Marta, and alludes to the national character of Poland through mushroomism.